Spain’s International Position (1782–1792) in the Light of the “Pamiętnik Historyczno-Polityczny” - Stroynowski, Andrzej (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
Due to the volumetric framework, the article focuses on only two factors that shaped Spain’s international position: the effectiveness of the foreign policy of its kings and the state’s military capabilities. However, the issues related to the internal policy of the rulers of Spain, the effects of which have also influenced the position of the state, mainly on the assessment of the Enlightenment elites of Europe, were omitted. The general tone of the reports of the “Pamiętnik Historyczno-Polityczny” journal presented Spain as a weak country in the international arena, increasingly dependent on French aid and unable to compete with England.